Contribution to the study of segmental cesarean surgery - Bazul, Víctor Manuel (1941)
The progress of obtetricia recently, shows a strong orientation toward surgery, prone, as expected, to replace old methods, inspired not only by the desire to save the life of the mother and the fetus, but also in preventing serious accidents and serious complications of pregnancy or childbirth, often consequences of the application of non-surgical procedures.